Handbook of antennas for EMC - Macnamara, Thereza; McAuley, John (Artech House antennas and electromagnetics analysis library., 2018)
Offering a thorough understanding of the practical aspects and underpinnings of antennas in EMC systems, this invaluable resource provides the knowledge needed to determine the right antenna for specific applications and offers guidance in conducting EMC testing. --